Pengembangan Flipbook Keanekaragaman Serangga Permukaan Tanah - Zico Fakhrur Rozi; Merti Triyanti; Diana Sari; Nugroho Aji Waluyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the diversity of ground insects and develop a flipbook in Sumberharta Village, Musi Rawas Regency. The method used is VES (Visual Encounter Survey). The ecological index was analyzed using the Shannon Wiener formula. The data collection on the development of the ground surface insect flipbook in Sumberharta Village, Musi Rawas Regency, refers to the stages of development research according to Borg & Gall. The results showed that the diversity of soil surface insects in Sumberharta village had an H value index of 1.036 and a uniformity of 0.154. The results of the flipbook development carried out by three validators and the practicality test of Biology Education students of STKIP-PGRI Lubuklinggau through small group trials of 20 people showed that the flipbook developed obtained a score of 88.2%. In conclusion, the diversity of soil surface insects in Sumberharta village is low, with the index value in the small and depressed category. The flipbook developed is very feasible and practical. Keywords: Development, Flipbook, Diversity